The Psychologist and the Foeign Language Teacher - Rivers, W.M. Wilga M. Rivers (Chicago: The University of Chicago Press, 1964)
Examines the underlying principles of today's audio-lingual method of language instruction in view of current theories of learning
include appendix, bibliographical reference and index